Synthesis of pure stereoisomers of benzo[b]thienyl dehydrophenylalanines by Suzuki cross-coupling. Preliminary studies of antimicrobial activity - Abreu, Ana S. (2008)
Several benzo[b]thienyldehydrophenylalanines were synthesized from pure stereoisomers of the methyl ester of N-(tertbutoxycarbonyl)- b-bromodehydrophenylalanine as an extension of our previously reported method for the synthesis of dehydrotryptophan analogues to dehydrophenylalanine derivatives. The latter were obtained in high yields by N-deprotection and bromination of N,N-bis-(tertbutoxycarbonyl)-( Z)-dehydrophenylalanine using TFA and NBS. This was carried out in two steps or in a one pot procedure resulting in different E/Z ratios. These compounds were coupled under Suzuki cross-coupling conditions [Pd(PPh3)4, Na2CO3, DME/H2O] with several boronic benzo[b]thienyl acids in good to high yields maintaining the stereochemistry of the starting materials. The best yields were obtained when the boronic acid was in position 7 of the benzo[b]thiophene and with the E isomer of the brominated dehydrophenylalanine. In some cases it was possible to increase the lower yields by changing the Pd source to PdCl2(PPh3)2. A model dipeptide was prepared coupling a benzo[b]thienyldehydrophenylalanine with the methyl ester of alanine. Preliminary antimicrobial studies were performed with both isomers of one of the b, b-diaryldehydroalanines obtained. The results show that the compounds are selective and very active (very low MICs) against Gram positive bacteria (B. cereus and B. subtilis) the Z-isomer being more active. The compounds are also active against Candida albicans presenting similar MICs.